2021
DOI: 10.1186/s12968-021-00802-8
|View full text |Cite
|
Sign up to set email alerts
|

Global, segmental and layer specific analysis of myocardial involvement in Duchenne muscular dystrophy by cardiovascular magnetic resonance native T1 mapping

Abstract: Background Progressive cardiomyopathy accounts for almost all mortality among Duchenne muscular dystrophy (DMD) patients.‍ Thus, our aim was to comprehensively characterize myocardial involvement by investigating the heterogeneity of native T1 mapping in DMD patients using global and regional (including segmental and layer-specific) analysis across a large cohort. Methods We prospectively enrolled 99 DMD patients (8.8 ± 2.5 years) and 25 matched ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…Diffuse fibrosis has been previously observed in patients with MD using native (noncontrast) T1 mapping compared with healthy controls. 54 , 55 In contrast to prior investigations, our ECV‐based assessment of diffuse fibrosis did not reveal elevated values in our MD cohorts relative to healthy controls. It is important to recognize a priori excluded segments with replacement fibrosis, isolating analysis to segments not already classified as abnormal by LGE‐based techniques.…”
Section: Discussioncontrasting
confidence: 99%
“…Diffuse fibrosis has been previously observed in patients with MD using native (noncontrast) T1 mapping compared with healthy controls. 54 , 55 In contrast to prior investigations, our ECV‐based assessment of diffuse fibrosis did not reveal elevated values in our MD cohorts relative to healthy controls. It is important to recognize a priori excluded segments with replacement fibrosis, isolating analysis to segments not already classified as abnormal by LGE‐based techniques.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, native T1 mapping allows the quantification of myocardial fibrosis without the administration of GBCAs. Previous research has demonstrated an increase in the native T1 value in DMD patients, which is related to the presence of myocardial fibrosis and LGE [ 17 , 18 ]. As a result, our study aimed to explore whether different combinations of non-contrast CMR parameters could be utilised as surrogates for LGE to predict the occurrence of LGE in DMD patients, thereby reducing the need for GBCAs and scanning time.…”
Section: Introductionmentioning
confidence: 99%